A Novel Antireflux Technique for Orthotopic Ileal Bladder Substitutes—Flat-Segment Technique: Preliminary Results. (26th July 2011) - ElFayoumy, Hany; Abou-Elela, Ashraf; Orban, Tamer; Emran, Ashraf; Elghoneimy, Mohamed; Morsy, Ahmed
Abstract : Objective . Although a large debate exists regarding the need for reflux prevention in ileal orthotopic neobladders, it is our policy to continue performing nonrefluxing ureteroileal anastomoses for our patients. An ideal uretero-ileal anastomosis must be simple, nonrefluxing, as well as non-obstructive. Here, we present a new antireflux mechanism for orthotopic ileal neobladders. Methods . 12 radical cystectomy patients for muscle invasive bladder cancer were candidates for orthotopic urinary diversion and underwent a non-refluxing uretero-ileal anastomosis using the flat-segment technique with a follow up of 6 to 18 months. Results . Preliminary results after the short-term followup showed that the success rate in reflux prevention was 92% and no cases of obstruction. The upper tracts were preserved or improved in all 12 patients. Operative time for neobladder creation ranged between 120–240 minutes, with a mean of 165 minutes (±36 minutes). No diversion-related complications. Conclusions . Based on our early data, we believe that the flat-segment uretero-ileal anastomosis technique for reflux prevention in orthotopic ileal bladder substitutes is simple, easy to learn and carries no additional morbidity to a standard refluxing uretero-ileal anastomosis, but has the advantage of effective reflux prevention. A longer follow-up period study with more patient numbers is ongoing.